Sero-Epidemiological Study of Hepatitis B and C Viruses among HIV-Positive Individuals Attending State Hospital Asaba, Nigeria - Udeze, O. A.; Ubamadu, U. P.; Olayemi, O. E.; Ajogbeje, O. O. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2017)
Hepatitis B and C virus infections are common among HIV-infected individuals. This study aimed at determining dual and triple infection rates of these viruses and correlating with immune status (CD4+ count) of HIV-infected individuals attending State Hospital Asaba, Nigeria. Blood samples and socio-demographic data were collected from 182 HIVinfected participants. HBsAg and anti-HCV antibody levels in blood samples were detected using Enzyme Linked Immunosorbent Assay (ELISA). Dual (HIV-HBV, HIV-HCV) and triple (HIV-HBV-HCV) infections were 6.6%, 6.6% and 0.6% respectively. HCV infection was strongly associated with gender, age and CD4+ count of the participants. Baseline screening of HIV-infected persons is recommended for early detection and appropriate treatment options.